Building surveys - Glover, P. V. (2023)
"Building Surveys has been a trusted guide for both students and professionals for nearly 40 years, evolving to address the challenges and responsibilities of the building surveying role. It covers everything needed for initial inspections such as equipment, know-how and procedures to writing an accurate report. This updated edition features new material on modern methods of construction, new sustainable materials, new surveying technologies, and industry developments in the wake of the Grenfell Fire. Essential reading for building construction students, professional surveyors, and others who may be required to inspect and report on buildings"--
Includes bibliographical references and index.
Keywords: Building inspection